A Survey on Design Methods for Secure Software Development (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2017)
Software provide services that may come with some vulnerabilities or risks. Attackers perform actions that break security of system through threats and cause a failure. To avoid security vulnerability, there are many security-specific concepts that should be determined as requirements during software development life cycle in order to deliver a strong and secure software. This paper first, survey a number of existing processes, life cycle and methodologies needed for developing secure software based on the related published works. It starts by presenting the most relevant Secure Software Development Lifecycles, a comparison between the main security features for each process is proposed. The results of the comparison will give the software developer with a guideline which will help on selecting the best secure process. Second, the paper list a set of the most widely used specification languages with the advantages and disadvantages for each.